PENGARUH SISTEM PENGENDALIAN INTERNAL DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN (STUDY EMPIRIS PADA SKPD KABUPATEN LOMBOK TENGAH) - Dini Ariani Putri; M. Cholid Mawardi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine the Effect of Internal Control Systems and Accounting Information Systems on the Quality of Financial Statements (Empirical Study of SKPD Lombok Tengah District). Based on the type of research, this research is included in quantitative research. The population in this study is the regional work unit (SKPD) of Central Lombok Regency. The number of samples in this study were 47 respondents with a purposive sampling technique, then the types and sources of data are primary data. Data collection methods in this study were obtained through questionnaires consisting of 27 statement items and were processed with the help of the SPSS program. Based on the results of data analysis using multiple linear regression models shows that simultaneously internal control system variables and accounting information systems have a significant effect on the quality of financial statements. Partially, the internal control system has a significant positive effect on the quality of financial statements. Partially the accounting information system has a significant positive effect on the quality of financial statements.Keywords: Internal Control Systems, Accounting Information Systems, Quality of Financial Statements.